2002
DOI: 10.1103/physrevlett.89.215502
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Dendrite Tip Splitting in Deeply Undercooled, Ultrahigh Purity Cu

Abstract: In a recent paper we used a phase-field model of solidification in deeply undercooled pure melts to show that a kinetic instability could result in dendrite tip splitting, and we speculated that such tip splitting could give rise to the phenomenon of spontaneous grain refinement. Here we present evidence, from the as-solidified microstructure of deeply undercooled ultrahigh purity Cu, of what appears to be dendrite tip splitting during recalescence. The significance of this finding in a nongrain refined sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 18 publications
(22 reference statements)
5
23
0
1
Order By: Relevance
“…Specifically, we have suggested that a tip-splitting instability at the dendrite tip leads to the growth of an unstable "dendritic seaweed" structure, which subsequently remelts to give the observed grain-refinement. Phase-field modeling of the thermally controlled solidification of a pure material at high undercooling [29] appear to support this suggestion, as does the observation, in deeply undercooled ultra-high purity Cu, of a "frozen in" seaweed morphology [30] above some critical undercooling. Moreover, above this critical undercooling a discontinuity in the velocity-undercooling curve was observed identical in character to that found in materials that display spontaneous grain refinement.…”
Section: Introductionsupporting
confidence: 61%
“…Specifically, we have suggested that a tip-splitting instability at the dendrite tip leads to the growth of an unstable "dendritic seaweed" structure, which subsequently remelts to give the observed grain-refinement. Phase-field modeling of the thermally controlled solidification of a pure material at high undercooling [29] appear to support this suggestion, as does the observation, in deeply undercooled ultra-high purity Cu, of a "frozen in" seaweed morphology [30] above some critical undercooling. Moreover, above this critical undercooling a discontinuity in the velocity-undercooling curve was observed identical in character to that found in materials that display spontaneous grain refinement.…”
Section: Introductionsupporting
confidence: 61%
“…marginal stability, growth at the extremum and even constant ρ appear to yield growth velocities displaying a power law dependence on Δ). Moreover, although experimental data [39,40,41,42 ] is only available for free dendritic growth in 3-dimesions, experimental velocityundercooling curves for a wide range of materials show a very similar type dependence.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of Ni 3 Ge, it appears that recrystallization is not suppressed until the cooling rate exceeds 42,000 K s À1 , wherein the observed primary solidification morphology is dendritic seaweed. Secondly, we note that [23] observed recrystallization grain refinement at low undercooling while in contrast [22] observed it at high undercooling but only at undercoolings higher than those required for the transformation to seaweed morphologies. In contrast, in this study we observe recrystallization grain refinement at lower undercoolings than the transformation to dendritic seaweed.…”
Section: Discussionmentioning
confidence: 93%
“…Conversely, in the immediately smaller size fraction (c: 53 to 38 lm, 42,000 to 62,000 K s À1 ) we see the clear development of dendritic seaweed, a morphology observed only at very large departures from equilibrium. [22,23] The histogram of grain orientations for the material in the 75 to 53 lm sieve fraction is shown in Figure 5(a), from which it is clear that the majority of grain boundary misorientations are either <10 deg or close to 60 deg. This is not the distribution that would be expected due to randomly nucleated grains.…”
Section: Resultsmentioning
confidence: 99%